Modern Apocrypha as an Example of Cultural Memory ‘in Action’ - Jankowska, Małgorzata (Załącznik Kulturoznawczy, 2023)
The aim of this paper is to analyze the role modern apocrypha play in the processes of collective remembering. From the perspective of cultural studies the modern apocrypha can be seen not only as literary or religious texts but also as an important element of cultural autocommunication. And if we understand autocommunication as a crucial mechanism of cultural memory, we can describe intertextuality (which is a form of cultural autocommunication) as an autoimmune technique of preventing the basic cultural meanings from the oblivion.The canon is a basic tool of collective memory in the so called ‘literate cultures’ or ‘Cultures of the Book’. That is the reason why the apocrypha, which deal with canonical contents, build the unique set of texts playing an essential role in protecting the source myth and tradition from the ‘semiotic death’.